Dihuangzicao Granules Regulate the AGE/RAGE/NF-κB Signaling Pathway to Inhibit Inflammation in Psoriatic Mice via Network Pharmacology and Experimental Validation - Lyu, Chong; Qiao, Xianhua; Shi, Zhe; Gao, Juanjuan; Li, Xiao; Jiang, Shibin; Wang, Chengcheng (Combinatorial Chemistry & High Throughput Screening, 2025)
AimPsoriasis is an immune-mediated skin disease that occurs worldwide and is characterized by high prevalence and chronicity. Psoriasis has a complex pathogenesis and is difficult to cure. Therefore, continuous exploration of the pathogenesis of psoriasis and the search for new drug treatment methods are crucial for improving treatment efficiency and reducing psychological damage to psoriasis patients. The active ingredients in Dihuang Zicao granules (DHZCG) can effectively treat psoriasis. Therefore, this study aimed to analyze the active ingredients of DHZCG and their potential mechanisms for treating psoriasis.MethodsThe effective components of DHZCG were screened via the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP). Genetic information for psoriasis was retrieved from the GeneCards, OMIM and DisGENET databases. Protein-Protein Interaction (PPI) analysis was performed, and component‒target‒disease networks were constructed. Important molecular biological processes and signaling pathways were screened via GO and KEGG analyses. Molecular docking of the active ingredients and key targets was performed via AutoDock Vina (1.1.2). A mouse model of psoriasis was established and divided into a control group, model group, low-dose DHZCG group (L-DHZCG), medium-dose DHZCG group (M-DHZCG), and high-dose DHZCG group (H-DHZCG). Hematoxylin and Eosin (HE) staining was performed to determine the pathological changes in the skin of each group of mice, and the Psoriasis Area Severity Index (PASI) score was used to assess skin damage. ELISA and RT‒PCR were used to measure the levels of the inflammatory factors TNF-a, IL-17A, and IL-23 in the serum and skin tissue of the mice, respectively. Western blotting was used to analyze the expression of proteins related to the AGE/RAGE signaling pathway. Immunofluorescence was used to examine the expression of the inflammatory factor NF-kB. Immunohistochemistry was used to measure IL-1β and TNF-a expression in skin tissues.ResultsSixty genes associated with psoriasis treatment by DHZCG, including core genes encoding IL-6, TNF-a, AKT1, IL-1β, TP53, NFKB1, BCL2, and MAPK3, were identified. Through the construction of a psoriasis mouse model, DHZCG treatment effectively reduced skin damage and significantly decreased the levels of the validated factors TNF-a, IL-17A, IL-23, IL-1b, and NF-kB in the serum and damaged skin. Furthermore, the reduction in the levels of these inflammatory factors by DHZCG is associated with the downregulation of the AGE/RAGE signaling pathway.ConclusionDHZCG reduces inflammation and alleviates psoriasis by downregulating the AGE/RAGE/NF-kB signaling pathway. This study is beneficial for providing a theoretical basis for the development of drugs for psoriasis and for offering personalized treatment strategies for the clinical management of psoriasis.
Keywords: AGE/RAGE/NF-κB